Revestimento bioativo a base de kombucha de Clitoria ternatea na conservação de salsicha - Souza, Bianca de (2025)
There is increasing global demand for packaging alternatives that reduce environmental impact. Edible films and coatings have emerged as viable solutions. These materials can be formulated using various polymers and supplemented with compounds that exhibit antioxidant and antimicrobial properties, which contribute to food preservation and shelf-life extension. The objective of this study was to develop a gelatin-pectin film incorporating kombucha from Clitoria ternatea flowers and apply it as a sausage coating. The films were characterized for thickness, mechanical properties, water vapor permeability, color, opacity, in vitro antimicrobial activity against Salmonella Typhimurium, Escherichia coli, and Staphylococcus aureus, total phenolic compound content, antioxidant activity, and total anthocyanin content. The films, in the form of coating, were applied to sausages previously contaminated with Escherichia coli and Staphylococcus aureus, and the shelf life was evaluated during refrigerated storage through lipid oxidation analysis and microorganism counts. The kombucha-containing film (KF) exhibited 103% greater elongation and an approximately 100% reduction in tensile strength compared to the control film (FC). KF presented a significant concentration of total phenolic compounds and anthocyanins, resulting in an average increase in antioxidant activity of 408% (DPPH assay) and 296% (FRAP assay) relative to FC. In contrast to FC, KF demonstrated antimicrobial activity against all tested microorganisms. Tests using the kombucha containing film as a coating on sausages demonstrated a significant reduction in lipid oxidation and in total bacterial and Enterobacteriaceae counts after 14 days of refrigerated storage. These findings reinforce the antioxidant and antimicrobial efficacy of the Clitoria ternatea kombucha-containing film and coating, supporting its potential for use in food preservation.